Analisis Faktor-Faktor Pemilihan Kafe yang Dikunjungi pada Masyarakat Sampit - Hasanah, Nur (Universitas Darwan Ali, 2023)
This research intends to uncover the characteristics that are considered when members of the Sampit community choose cafés to frequent. Participants who have been to cafes in the city of Sampit are the subjects of this investigation. Their ages vary from 16 to 55, and there were a total of 100 people who participated in the research. Non-random sampling combined with a purposive sampling methodology was employed as the method of sampling, and the questionnaire in the form of a Likert scale was used as the research instrument. Multiple linear regression is the approach of data analysis that is used here. According to the findings of the research conducted, the diversity of menus has a major impact on the choices made by customers when selecting a cafe in the city of Sampit to which they will pay a visit for the purpose of making purchases. When it comes to selecting a cafe to visit in the city of Sampit, a customer's choice to buy a drink or meal at a certain establishment is not significantly influenced by factors such as location, price, level of service, or ambiance.